KLF2 Inhibits the Migration and Invasion of Prostate Cancer Cells by Downregulating MMP2 - Wang, Binshuai (Am J Mens Health, 2018)
KLF2, a member of the Kruppel-like factor (KLF) family, is thought to be a tumor suppressor in many kinds of malignant tumors. Its functions in prostate cancer (PCa) are unknown. This study aimed to explore the role of KLF2 in the migration and invasion of PCa cells. The expression of KLF2 was measured by immunohistochemistry in PCa tissues and in paired non-tumor tissues. KLF2 and MMP2 expression in cells was measured by Western blot and RT-qPCR. Adenoviruses and siRNAs were used in cell function tests to investigate the role of KLF2 in regulating MMP2. Interactions between KLF2 and MMP2 were analyzed by a luciferase activity assay. The present study, for the first time, identified that KLF2 was downregulated both in PCa clinical tissue samples and in cancer cell lines. The overexpression of KLF2 inhibited the migration and invasion of PCa cells via the suppression of MMP2.This study demonstrates that KLF2 might act as a tumor suppressor gene in PCa and that the pharmaceutical upregulation of KLF2 may be a potential approach for treatment.